Supporting the adoption of a digital emergency response system in Costa Rica - CGIAR Research Program on Climate Change, Agriculture and Food Security; Bioversity International (2016)
In the past, the Ministry of Agriculture and Livestock (MoAL) of Costa Rica worked with paper-based data, which hindered their response to emergencies. To increase adequate emergency responses to extreme climate events, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and Bioversity International assisted the local government of Siquirres by piloting a digital system for data collection and decision-making. This pilot was scaled up to collect data on 3575 affected households and inventory the USD 57 million of damages after Hurricane Otto. It enabled the MoAL to draft a detailed response plan to both restore agricultural infrastructure and increase climate resilience.